PELATIHAN DAN PENDAMPINGAN PENGELOLAAN MEDIA DIGITAL DI PAROKI MATER DEI MADIUN - Setiyo, Lorensius Anang; Djokowidodo, Agustinus; Andoro, Ign. F. Bayu (Fakultas Bisnis, Universitas Katolik Widya Mandala Surabaya, 2023)
During a pandemic it is not permissible to carry out activities that cause crowds. Worship was diverted to live streaming, as well as worship activities at the Mater Dei Madiun Catholic Church. The creation of social media, websites and YouTube channels has been carried out, but their use has not been maximized. Utilization of the new digital media channel YouTube, and even then live streaming is only used. The problem faced is that social media and websites owned by the parish are not optimal yet, there is no content managed by category groups. The outputs produced in this activity include maximizing the use of digital media and the formation of digital media managers at Mater Dei Madiun Parish.